2019
DOI: 10.22146/studipemudaugm.39347
|View full text |Cite
|
Sign up to set email alerts
|

Fintech Waqaf: Solusi Permodalan Perusahaan Startup Wirausaha Muda

Abstract: Money waqaf in Indonesia has a huge potential. Despite the fact, this huge potential has not been organized and utilized optimally by the waqaf management agency. Another problem faced in waqaf money is the difficulties in integrate the system of funding, financing, mauquf alaih, and distribute the beneficiaries. In the present era, waqaf in Indonesia has not been digitalized and has not used the Financial Technology (FinTech) system, so it is less economically and inefficient. The expected benefits of the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 2 publications
0
8
0
13
Order By: Relevance
“…Added to those described above, the Open Unemployment Rate by age group 15-29, classified as youth, has the largest percentage of 50.39 percent (BPS, 2019). This is as according to Ryandono (2018) on the fact the world of work shows that job seekers or the largest open unemployed in Indonesia are youth, as shown in Table 1. The problem of unemployment in an Islamic perspective is a condition where a person does not want to utilize his physical and spiritual potential in realizing a benefit that is justified by Sharia.…”
Section: Introductionmentioning
confidence: 75%
“…Added to those described above, the Open Unemployment Rate by age group 15-29, classified as youth, has the largest percentage of 50.39 percent (BPS, 2019). This is as according to Ryandono (2018) on the fact the world of work shows that job seekers or the largest open unemployed in Indonesia are youth, as shown in Table 1. The problem of unemployment in an Islamic perspective is a condition where a person does not want to utilize his physical and spiritual potential in realizing a benefit that is justified by Sharia.…”
Section: Introductionmentioning
confidence: 75%
“…Research that focuses on fintech usage delivered by Kim, Won-Jun, and Rusydiana [25] [26] [27]. A conceptual framework of Model Sharia Financial Technology that integrated start-up fintech and waqf funds [12]. This study suggested a model become the solution of financing start-up companies based on waqf funds.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Firmansyah & Ramdani (2018) explain that the Islamic FinTech startup plays an essential role in fostering financial inclusion and decreasing social problems in Indonesia by developing new technology and a new business model. The five elements in the fintech ecosystem, according to (Ryandono, 2018) are first, Fintech for startups (payments, loans, crowdfunding, capital markets, and insurance companies); second, technology developers (e.g., big data analysis, cloud computing, cryptocurrency, and social media developers; third, government (e.g., financial regulators and legislative bodies); fourth, financial customers (e.g., individuals and organizations), and; fifth, traditional financial institutions (e.g., traditional banks, insurance companies, stockbrokers and venture capital) Bank Indonesia Regulation Number 19/12/PBI/2017 concerning Financial Technology Implementation can carry out financial activities in the form of: first, payment systems; second, market support; third, investment management and risk management, fourth, loans, financing and capital supply, fifth, other financial services. Er and Mutlu (2017) examined the "Financial Inclusion and Islamic Finance: A Survey of Islamic Financial Literacy Index."…”
Section: Sharia Financial Technologymentioning
confidence: 99%